Virtuální umma: islám a islámští radikálové v kyberprostoru = The virtual umma : Islam and Islamic radicals in cyberspace - Kovács, Attila (Religio, 2001)
I am interested here in the impact of information technology on the Islam and Islamic radicalism and the creation an virtual Islamic world-wide community (virtual umma). There are difficult and controversal relationships between Islam and modernity, Islamic radicalism, hi-tech, and information technology. Like printing, telephone, radio-broadcasting, and later satellite dish, or cable television in their initial introduction to the Arab-Islamic world, information technology has been a focus of controversy, a tool of liberalization for some, yet another form of westernization and secularization to others, or a third, alternativě way for Islamists, and a source of political and social instability in the region. As in many parts of the world, the Internet has been expanding very fast in the Arab-Islamic world, the number of Internet users rose dramatically. Islamists and secularist thinkers have also created Web sites to project their opinions on a variety of Islamic issues like Qur'an, hadith, on-line Islamic preaching, and Islamic call (daʿwa). The Internet had been Islamized. Some Islamic terrorist groups use information technology or hi-tech to communication or propaganda with a hi level of professionality. For Islamic terrorisls like Osama Bin Laden, become the Internet an excellent medium for the new form of jihad known as "netwar" or "cyberwar". The most important function of the search an Islamic cyber community is the realization of the Islamist political project: creation an (nor virtually) unity of the world-wide Islamic umma, which will be the first step to the real unity of Islam(ists).